Evaluation of Serum Biochemical Parameters, Visfatin, and C-Reactive Protein Concentrations in Obese Versus Non-Obese Cats - Çıkma, M; Gülersoy, E (Journal of the Hellenic Veterinary Medical Society, 2026)
Obesity in cats is associated with chronic low-grade systemic inflammation, driven by an acute-phase response from adipose tissue. In addition to increasing disease risk, obesity also reduces lifespan. This study aimed, for the first time, to evaluate visfatin levels in clinically healthy-appearing obese cats, assess their relationship with C-reactive protein (CRP) and selected biochemical parameters, and explore their utility as early biomarkers of obesity-related changes. A total of 194 cats presented for routine health checks and vaccinations were screened; after applying inclusion and exclusion criteria, 40 were assigned to the Obese group and 20 to the Control group. All cats underwent physical examination, complete blood count (CBC), serum biochemistry analysis, and measurements of serum CRP and visfatin levels. Body condition score and body weight were significantly higher in the Obese group (p<0.000). While CBC values remained within reference ranges, monocyte (p<0.027) and RDW (p<0.000) levels were significantly elevated in obese cats. Although serum biochemistry values were within reference ranges, the Obese group had significantly higher BUN (p<0.012) and total bilirubin (p<0.000), and lower ALT levels (p<0.035). Serum CRP (p<0.000) and visfatin (p<0.001) levels were also markedly elevated in obese cats. Diagnostic evaluation indicated that monocyte count, AST, LDH, and GGT had acceptable value, RDW, BUN, and visfatin had excellent value, and CRP and total bilirubin demonstrated outstanding diagnostic utility for identifying subclinical inflammation. In conclusion, the findings highlight the persistence of chronic low-grade inflammation in obese cats, even in the absence of clinical signs. Routine monitoring of CRP and visfatin, along with dietary and behavioral interventions, may be crucial for early detection and management of obesity and its related comorbidities in at-risk cats.